Acinetobacter baumannii NCIMB8209: a rare environmental strain displaying extensive insertion sequence-mediated genome remodeling resulting in the loss of exposed cell structures and defensive mechanisms - Repizo, Guillermo Daniel (2020)
Fil: Fil: Repizo, Guillermo Daniel. Universidad Nacional de Rosario. Facultad de Ciencias Bioquímicas y Farmacéuticas. Instituto de Biología Molecular y Celular de Rosario (IBR -CONICET); Argentina.